PENGARUH KEPERCAYAAN DAN LOYALITAS PELANGGAN TERHADAP KEPUTUSAN PEMBELIAN MAKANAN MENGGUNAKAN APLIKASI GRABFOOD - Megawati Dewi Yunitasari (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study examines the relationship between brand loyalty and brand trust on Grabfood customers' purchasing decisions. The research focuses on the various effects of product brand loyalty and brand trust on Grabfood customers' purchasing decisions. This study adopted a cross-sectional quantitative research design. In today's competitive business world, marketers and manufacturers of most brands now encounter multiple variables that not only influence customers' purchasing decisions, but also ensure their purchasing preferences. The variables used and relevant in this study are product brand loyalty, brand trust and purchase decision. When examining the relationship between these variables, the study found a positive relationship between brand loyalty, brand trust, and purchasing decisions.